Molecular targets and the use of biologics in the management of small bowel fibrosis in inflammatory bowel disease. Issue 3 (May 2021) - Abdulla, Muaad; Chew, Thean Soon
Abstract : Purpose of review: Small bowel fibrosis is a significant burden on Crohn's disease patients with limited effective medical treatments that then requires surgery. A better understanding of the molecular mechanisms causing fibrosis and the evidence of benefit of available biologics will potentially lighten this burden and avoid the need for surgery. Recent findings: Transforming growth factor-beta and it's associated pathways remain the central cog in the wheel of fibrosis formation. Various new enzymes, cellular pathways, interleukins and molecules have been associated with beneficial modification of the fibrotic process. Licensed biologics such as antitumour necrosis factors continue to show evidence of efficacy in the treatment of fibrostenotic small bowel disease as well as the newer biologics ustekinumab and vedolizumab. Summary: Fibrostenotic disease of the small bowel is a significant and common debilitating complication in Crohn's disease patients. Multiple new molecular targets have been identified that may prove to become effective therapies in future. Antitumour necrosis factors remain the treatment with the best available evidence to date in fibrostenotic Crohn's disease.